Self Healing: Terapi atau Rekreasi? - Anisa Mutohharoh (Journal of Sufism and Psychotherapy, 2022)
The use of the word healing is currently popular in Indonesian society, especially in various social media. Healing refers to activities to seek satisfaction such as: taking a walk, eating good food, or going to a cafe. This often leads to high costs. In addition, healing is also used as a way to break away from routine. The trend of healing is increasingly widespread, mainly because of the habits of the Indonesian people who are easily influenced. People who use this word are considered cool or great. Therefore, this study aims to clarify the term self-healing through the explanation of concepts according to psychology and Sufism so that people are no longer mistaken. The method used in this research is qualitative with the type of literature study (Library Research). Data sources come from news, books, journals, articles, and other relevant references. The result is that the word healing is different from recreation, where community activities that refer to traveling or using money to get satisfaction are not self-healing. Healing is a part of therapy that is often used by health practitioners, especially psychiatrists and clinical psychologists. The goal is to treat wounds or accept the past that has an impact on disturbed psychological conditions. Self-healing can be done without spending money with various techniques such as: relaxation, writing, mindfulness, positive self-talk, self-management, reading the Qur’an, and others.